A Guide to Event Study Methodology: Perspectives and Applications in Business Market Research - Khalid, Bilal (KKBS Journal of Business Administration and Accountancy, 2024)
This study presents a comprehensive methodological analysis of the model specifications, analysis process, and market application of event study. The study focused on technique’s efficacy in business performance research. Event studies are widely utilized for assessing the impact of specific business and management events, such as earnings announcements, mergers, and regulatory changes, on stock prices, providing a quantitative measure of market reactions. This study demonstrated a step-by-step process of conducting an event study by applying the Capital Asset Pricing Model (CAPM). The relevant event windows and data analysis process are discussed. This study reviews key applications of event studies in business research, highlighting their role in testing market efficiency, understanding investor behavior, and evaluating firm-specific events’ economic impact. Highlighted key applications include analyzing effects of business events such as earnings, dividends, and mergers announcements; testing market efficiency; studying investors’ behavior; and risk-return analysis. Some limitations of event study heighted include issues with model dependence, selection biases, and the challenges of accurately defining estimation and event windows. This study proposes the need for refining event study methodologies, emphasizing the potential of advanced econometrics, machine learning, and behavioral finance integration.